Learning the words: Supervising teachers and the language of impact in an initial teacher education programme - Brett, P.; Fitzallen, N.; Kilpatrick, S.; Morrison, Chad; Mainsbridge, C.; Reynolds, B.; Kertesz, J.; Quentin-Baxter, M. (Social Science Press, 2018)
© 2018 Social Science Press. The language of "impact" has been foregrounded in the recent lexicon of Australian initial teacher education (ITE). How teacher education programmes and supervising teachers identify and assess the impact of pre-service teachers' work with learners across a professional placement is a pressing issue for ITE providers. This paper reports on qualitative analysis of the language of supervising teachers' summative assessments of pre-service teachers' final-year professional experience placements in relation to impact. Analysis of written comments that addressed the Australian Professional Standards for Teachers Graduate Standards revealed that the language of impact is still emerging within the discourse of supervising teachers. This has professional learning implications for all ITE stakeholders.